Comparing the epidemiology, clinical characteristics and prognostic factors of acute myeloid leukemia with and without acute promyelocytic leukemia. (23rd January 2019) - Kamath, Geetanjali R; Tremblay, Douglas; Coltoff, Alexander; Caro, Jessica; Lancman, Guido; Bhalla, Sheena; Najfeld, Vesna; Mascarenhas, John; Taioli, Emanuela
Abstract: Acute promyelocytic leukemia (APL) is a particularly aggressive subtype of acute myeloid leukemia (AML), with high rates of early death. It is important to examine how epidemiological characteristics, clinical and treatment factors, cytogenetic and genetic data affect survival and differ between APL and non-APL AML patients. We analyzed population data from the New York State Cancer Registry to characterize AML including APL incidence rates by demographics. APL incidence rates were higher among Hispanics than non-Hispanics [incidence rate ratio = 1.22; 95% confidence interval (CI) = 1.02–1.43]; and among foreign-born than USA-born persons. APL incidence rates increased more rapidly through 1995–2014 than non-APL AML; and its frequency increased faster among foreign-born persons. In a hospital cohort of 390 AML patients, the risk of death was significantly higher among APL patients with FLT3-internal tandem duplications than those without [hazard ratio (HR) = 11.74; 95% CI = 1.03–134.5]; and among APL patients with secondary versus de novo disease (HR = 17.32; 95% CI = 1.56–192.1). Among non-APL AML patients, risk of death was significantly associated with prior chemotherapy with antitubulin agents after adjusting for age, gender and ethnicity (adjusted HR = 3.30; 95% CI = 1.49–7.32); and separately with older age, unfavorable cytogenetics and complex karyotype. This study highlights FLT3 -internal tandem duplications as a prognostic factor in APL and proposes consideration of prior antitubulin therapy as a prognostic factor in non-APL AML. Abstract : In this study, acute promyelocytic leukemia (APL) was more frequent among Hispanics and persons born outside the USA. Risk of death was increased among APL patients with FLT3-internal tandem duplications mutations and secondary leukemia, and among acute myeloid leukemia patients with prior chemotherapy with antitubulin agents.